Blended Learning During Pandemic Corona Virus: Teachers’ and Students’ Perceptions - Widyawan Kuncoro Aji; Hardiani Ardin; Muhammad Ahkam Arifin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The pandemic coronavirus is forcing educational institutions to shift rapidly to distance and online learning. It forces teachers and students to apply blended learning even though they may not be ready to teach and learn in fully online contexts. Hence, this research aims to explore teachers' and students' perceptions at Parahikma Institute of Indonesia regarding the use of blended learning as media learning during the pandemic coronavirus.  This research was a qualitative design applying phenomenology. The technique of selecting participants was convenience sampling. The participants of this study consist of nine students from the third, fifth, and seventh semesters who were enrolled in the English Education Department and three lecturers who taught English at Parahikma Institute of Indonesia. This study utilized semi-structured interviews as the single data collection method. The data collected were analyzed using thematic analysis. The result of this study covered two parts, namely the teachers' and students' perceptions. In terms of teachers’ perception, the teachers reported some advantages regarding blended learning such as effective learning, autonomous learning and easy to use. However, there were challenges for the teachers in teaching through blended learning such as poor internet connection, time-consuming, and less experience. On the contrary, regarding students’ perceptions, students also reported benefits the blended learning like flexible learning, motivation, interaction, and improving their ICT skills. In addition, poor internet connection and incomprehensible materials were considered as the problem that hampers their learning.